2019
DOI: 10.1002/cphc.201900380
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Diffusion Guided Design of Pt‐Based Alloys for Inhibition of Butadiene Over‐Hydrogenation

Abstract: Alloying Pt with other metals is an effective strategy to tune its performance towards selective hydrogenation reactions. Herein, we have demonstrated a process to screen Pt‐based alloys for inhibition of butadiene over‐hydrogenation with a model comprising isolated single atoms (ISA) embedded into Pt(111). DFT calculations reveal that the diffusion energy barrier of H co‐adsorbed with 1‐butene is a key parameter for the screening. The output from the ISA model was validated by testing several typical Pt‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Butadiene selective hydrogenation reaction is generally studied at lower temperatures (<423 K) and is often performed with excessive amounts of hydrogen (H 2 /BD > 15). 37 Butane formation can be observed 37,38 even at such mild reaction temperatures and with H 2 /BD ratios similar to those observed in naphtha steam-cracking applications, 39 situations where the selective hydrogenation of acetylene to ethylene or butadiene to butenes is necessary prior to downstream operations. Traditional butadiene selective hydrogenation catalysts include Cu/SiO 2 , 40 Pd/Al 2 O 3 , 41 and Pt-Ni/Al 2 O 3 , 42 while "single-atom alloy" (SAA)-supported metal catalysts composed of dilute solid solutions of precious metals (e.g., Pd or Pt) within transition-metal nanoparticles (e.g., Cu) have recently been studied as relevant selective hydrogenation catalysts.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Butadiene selective hydrogenation reaction is generally studied at lower temperatures (<423 K) and is often performed with excessive amounts of hydrogen (H 2 /BD > 15). 37 Butane formation can be observed 37,38 even at such mild reaction temperatures and with H 2 /BD ratios similar to those observed in naphtha steam-cracking applications, 39 situations where the selective hydrogenation of acetylene to ethylene or butadiene to butenes is necessary prior to downstream operations. Traditional butadiene selective hydrogenation catalysts include Cu/SiO 2 , 40 Pd/Al 2 O 3 , 41 and Pt-Ni/Al 2 O 3 , 42 while "single-atom alloy" (SAA)-supported metal catalysts composed of dilute solid solutions of precious metals (e.g., Pd or Pt) within transition-metal nanoparticles (e.g., Cu) have recently been studied as relevant selective hydrogenation catalysts.…”
Section: Introductionmentioning
confidence: 68%
“…Butadiene selective hydrogenation reaction is generally studied at lower temperatures (<423 K) and is often performed with excessive amounts of hydrogen (H 2 /BD > 15) . Butane formation can be observed , even at such mild reaction temperatures and with H 2 /BD ratios similar to those observed in naphtha steam-cracking applications, situations where the selective hydrogenation of acetylene to ethylene or butadiene to butenes is necessary prior to downstream operations. Traditional butadiene selective hydrogenation catalysts include Cu/SiO 2 , Pd/Al 2 O 3 , and Pt-Ni/Al 2 O 3 , while “single-atom alloy” (SAA)-supported metal catalysts composed of dilute solid solutions of precious metals (e.g., Pd or Pt) within transition-metal nanoparticles (e.g., Cu) have recently been studied as relevant selective hydrogenation catalysts. ,, Low-temperature (<423 K) butadiene selective hydrogenation reactivity over Pt–Cu SAA catalysts has been qualitatively correlated with the formation of hydrogen islands around Pt centers through hydrogen adsorption, scission, and subsequent adatom diffusion to proximal Cu centers; however, their applicability for higher temperatures has not been investigated and particularly not for near-stoichiometric hydrogen and butadiene partial pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al also observed this phenomenon and discovered that the hydrogen atom located near the adsorbate is the real bonding atom. [15] Accordingly, the activation energy is provided with respect to the reference energy of the co-adsorbed state in this study.…”
Section: Reaction Pathways For Hydrogenation Of Calmentioning
confidence: 99%
“…Conversely, density functional theory (DFT) is a powerful tool that can be used to investigate a detailed chemical reaction at the microscopic level. [13][14][15] To clarify the hydrogenation mechanism of CAL on Pt, Hu et al used a microkinetic model to investigate the reaction mechanism on flat Pt (111). [16,17] This pioneering work undoubtedly deepen our understanding on hydrogenation of 𝛼,𝛽-unsaturated aldehydes, especially on the 1,4-addition hydrogenation mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation